The Effect of Islamic Branding, Product Quality and Price on Consumer Purchase Decisions for Wardah Products in Semarang - Atika Lia Safitri; Ahmad Dwi Nurdiyanto (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to determine and explain the influence of Islamic branding, product quality and price on consumer purchasing decisions on Wardah products in Semarang. This study is a type of quantitative research. The determination of the number of samples in this study was calculated using the Lameshow formula. The sampling technique used in this study used a non-probability sampling technique with a purposive sampling determination of 97 respondents. Based on the results of the study, it shows that: Islamic branding and price have a significant influence on consumer purchasing decisions on Wardah products in Semarang. Product quality has no influence on consumer purchasing decisions on Wardah products in Semarang.